2001
DOI: 10.1037/0012-1649.37.4.539
|View full text |Cite
|
Sign up to set email alerts
|

Visual short-term memory in the first year of life: Capacity and recency effects.

Abstract: A span task was developed to assess the amount of information infants could hold in short-term memory. In this task, infants were presented with up to 4 items in succession and then tested for recognition by successively pairing each item with a novel one. A large sample of full-terms and low-birth-weight preterms (< 1,750 g) was tested longitudinally, at 5, 7, and 12 months of age. Results were similar for both groups: (a) Longer spans were more difficult, especially at the 2 younger ages; (b) memory capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 61 publications
6
89
2
Order By: Relevance
“…Detecting similarities and differences between items encountered at different times requires that the memory for one item is compared with a second item currently in view. Because young infants' shorter-term memory abilities are limited (Rose, Feldman, & Jankowski, 2001; Ross-Sheehy, Oakes, & Luck, 2003) and their longer-term memories are less detailed than are the longer-term memories of older infants (Wilk, Klein, & Rovee-Collier, 2001), young infants may not make effective comparisons between a remembered item and another item. Indeed, Needham and her colleagues observed that infants detected different commonalities among items as a function of the amount of time between encounters with those items.…”
mentioning
confidence: 99%
“…Detecting similarities and differences between items encountered at different times requires that the memory for one item is compared with a second item currently in view. Because young infants' shorter-term memory abilities are limited (Rose, Feldman, & Jankowski, 2001; Ross-Sheehy, Oakes, & Luck, 2003) and their longer-term memories are less detailed than are the longer-term memories of older infants (Wilk, Klein, & Rovee-Collier, 2001), young infants may not make effective comparisons between a remembered item and another item. Indeed, Needham and her colleagues observed that infants detected different commonalities among items as a function of the amount of time between encounters with those items.…”
mentioning
confidence: 99%
“…Specifically, they did not demonstrate recognition memory, despite the fact that the current paradigm was based on that used in Rose et al (2001). Importantly, there was a major methodological difference between the current study and that in Rose et al (2001).…”
Section: Discussionmentioning
confidence: 60%
“…Specifically, they did not demonstrate recognition memory, despite the fact that the current paradigm was based on that used in Rose et al (2001). Importantly, there was a major methodological difference between the current study and that in Rose et al (2001). In particular, Rose and colleagues used real three-dimensional objects in their recognition memory task, whereas static images of three-dimensional objects were used in the current study.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations